Hubungan Status Paritas, Status Gizi Ibu, dan Usia Kehamilan dengan Kejadian Berat Badan Lahir Rendah (BBLR) di RSUD Dr. R. Soedjono Selong - Bq. Nia Apriliana Putri; Lalu Irawan Surasmaji; Aena Mardiah; Ida Ayu Made Mahayani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Low Birth Weight (LBW) is one of the main causes of neonatal morbidity and mortality and remains a public health problem. The incidence of LBW is influenced by various multifactorial factors involving maternal, fetal, and environmental factors. This study aims to determine the relationship between parity status, maternal nutritional status, and gestational age with the incidence of LBW at Dr. R. Soedjono Selong Regional General Hospital. This observational analytical study with a cross-sectional design involved 86 mothers who gave birth through simple random sampling from medical records in 2024. Data were analyzed univariately, bivariately using the Chi-square test, and multivariately using logistic regression. The results showed a prevalence of LBW of 26.7%. Bivariate analysis showed that parity status was not significantly associated with LBW (p = 0.218), while maternal nutritional status (p = 0.007) and gestational age (p = 0.000) were significantly associated with the incidence of LBW. In multivariate analysis, gestational age was the most dominant factor (PR = 18.945; p = 0.000), while maternal nutritional status only showed a trend toward increased risk (p = 0.105), and parity status had no significant effect. Gestational age was the primary determinant of LBW incidence. Maternal nutritional status was associated with LBW, while parity showed no significant association.